Identification of LSM Family Members as Novel Unfavorable Biomarkers in Hepatocellular Carcinoma - Zhuang, Hongkai; Chen, Bo; Tang, Chenwei; Chen, Xinming; Tan, Wenliang; Yang, Lei; Xie, Zhiqin; Ma, Xiaowu; Wang, Qingbin; Zhang, Chuanzhao; Shang, Changzhen; Chen, Yajin (Frontiers in Oncology, 2022)
Background: Smith-like (LSM) family members play critical roles in multiple oncologic processes in several types of malignancies. Study on LSM family members in HCC might provide new insights into the tumorigenesis and therapeutic strategies of HCC. Methods: The clinical significance and oncologic biological functions of LSM family members were assessed through multiple bioinformatics methods and in vitro studies. The potential correlation between LSM family members and tumor immunity were also investigated using single sample gene set enrichment analysis (ssGSEA) and the ESTIMATE algorithm. Results: LSM family members overexpression in HCC significantly correlated with poor clinical outcomes such as higher TNM stage, advanced histologic grade, and worse prognosis. A risk score system based on LSM5, LSM10, LSM12 and LSM14B showed a reliable predictive ability for OS of HCC patients. Functional enrichment analysis demonstrated that LSM family members overexpression were all involved in cell cycle related biological processes. Besides, LSM12, LSM14A and LSM14B were found significantly associated with PI3K-Akt-mTOR and T cell receptor signaling pathways. Tumors with LSM12, LSM14A and LSM14B overexpression exhibited lower infiltration of activated CD8+ T cell with declined cytolytic activity and immune score, but increased infiltration of Th2 cell and Th2/Th1. LSM12, LSM14A and LSM14B overexpression also associated with higher tumor-related immune checkpoints (e.g. PD-L1, B7-H3 and PVR) expression and increased therapeutic insensitivity to immune checkpoint blockade (ICB). Moreover, the knockdown of LSM12, LSM14A and LSM14B significantly inhibited the proliferation and invasion of HCC cells. Conclusion: This study systematically investigated the expression pattern and biological values of LSM family members in HCC, identified LSM family members as novel therapeutic targets in HCC.